Force, orientation and position control in redundant manipulators in prioritized scheme with null space compliance. (April 2019) - Karami, Abbas; Sadeghian, Hamid; Keshmiri, Mehid; Oriolo, Giuseppe
Abstract: This paper addresses the problem of executing multiple prioritized tasks for robot manipulators with compliant behavior in the remaining null space. A novel controller–observer is proposed to ensure accurate accomplishment of various tasks based on a predefined hierarchy using a new priority assignment approach. Force control, position control and orientation control are considered. Moreover, a compliant behavior is imposed in the null space to handle physical interaction without using joint torque measurements. Asymptotic stability of the task space error and external torque estimation error during executing multiple tasks are shown. The performance of the proposed approach is evaluated on a 7R light weight robot arm by several case studies. Highlights: A novel strict prioritization method is employed. A new controller-observer is suggested for executing multiple different tasks. Accidental physical interaction with robot is estimated precisely through observer. Redundant robot stability in any arbitrary task combination is shown analytically. Null-space compliance is considered for handling accidental interactions. The proposed method implemented in multiple scenarios in KUKA LWR IV.